Serum chloride levels in critical illness—the hidden story - Carmen Andrea Pfortmueller; Dominik Uehlinger; Stephan von Haehling; Joerg Christian Schefold (Intensive Care Medicine Experimental, 2018)
Abstract Chloride is the principal anion of the extracellular fluid and vital for both serum electroneutrality and acid-base homeostasis. The aim of this review is to investigate the relevance of dyschloremia in the critically ill. An extensive literature research was conducted on www.pubmed.org. In addition, the references of included articles were searched for further possible investigation regarding chloride. Articles investigating the relevance of dyschloremia in the critically ill were included. All articles were screened in regard to dyschloremia in the critically ill. Chloride is essential for blood pressure control, decarboxylation/gas transport, renal function, and gastrointestinal homeostasis. “Dyschloremia,” i.e., serum chloride levels not within the limits of normal, may commonly be observed on ICUs and appear mainly induced by iatrogenic measures (i.e., infusion of chloride-rich fluids). Hypo- and hyperchloremia appear linked to increased mortality in defined ICU populations, but evidence is sparse. Data show that hyperchloremia may not only be linked to hyperchloremic metabolic acidosis, but also to increased hemodynamic instability and vasopressor need (e.g., in patients after major surgery). Nevertheless, it is currently unknown whether such effects would be directly or indirectly mediated. Moreover, recent evidence points to an increased incidence of acute kidney injury and need for renal replacement therapy in patients with advanced hyperchloremia. Current knowledge on chloride is largely limited by heterogeneous trial design and mostly abundant data on specific fluid replacement strategies. The aim of this review is to summarize key consequences of chloride in critical illness and to discuss implications for daily clinical practice and future research.